Intrinsic Amorphous Silicon Bilayers for Effective Surface Passivation in Silicon Heterojunction Solar Cells: A Comparative Study of Interfacial Layers - Sai, Hitoshi; Hsu, Hung-Jung; Chen, Po-Wei; Chen, Pei-Ling; Matsui, Takuya (Physica status solidi. A, Applications and materials science, 2021)
The impact of intrinsic amorphous silicon bilayers in amorphous silicon/crystalline silicon (a‐Si:H/c‐Si) heterojunction solar cells is investigated. Intrinsic a‐Si:H films with a wide range of film densities and hydrogen contents are prepared via a plasma‐enhanced chemical vapor deposition (PECVD) technique by modifying various process parameters. For silicon heterojunction (SHJ) solar cells with a‐Si:H films applied as single i‐layers, the resulting surface passivation at the a‐Si:H/c‐Si interface is poor. However, surface passivation is significantly improved by applying intrinsic bilayers, which are composed of a porous interfacial layer (≈2 nm) and an overlying dense layer (≈8 nm). The microstructure factor R* of the interfacial a‐Si:H layer, which is related to the SiH bond microstructure and determined by infrared absorption spectroscopy, closely correlates to the surface passivation capability of the bilayers. A variety of PECVD process parameters (temperature, pressure, or precursor gas species) can be utilized to grow an interfacial layer for good surface passivation, provided that its R* is controlled within a suitable range. This indicates that R* is a key universal parameter for optimizing i‐bilayers and realizing high‐efficiency SHJ solar cells. Herein, silicon heterojunction solar cells with intrinsic amorphous silicon (a‐Si:H) bilayers are investigated. The microstructure factor R* of the interfacial a‐Si:H layer, which is related to the SiH bond microstructure, closely correlates to the surface passivation, and must be controlled within a suitable range for realizing high‐efficiency silicon heterojunction solar cells.